The logic of syntactic priming and acceptability judgments. (10th November 2017) - Gaston, Phoebe; Huang, Nick; Phillips, Colin
Abstract: A critical flaw in Branigan & Pickering's (B&P's) advocacy of structural priming is the absence of a theory of priming. This undermines their claims about the value of priming as a methodology. In contrast, acceptability judgments enable clearer inferences about structure. It is important to engage thoroughly with the logic behind different structural diagnostics.